The Influence of TikTok Information Quality Towards Destination Image Formation in Greater Bandung - Abadi, Muhammad Alif Fairuz; Qastharin, Annisa Rahmani (Journal of Business and Management, 2021)
Covid-19 pandemic affects tourism sectors, especially for Greater Bandung, which is a national strategic destination. Improving destination image is an essential strategy for tourism recovery strategy given the perceived belief and overall understanding of a tourist destination in the destination's image. This research will determine the role of TikTok content quality towards destination image formation in Greater Bandung. Primary research data was carried out using an online survey method related to variable information quality and destination image formation. This research was carried out from May to July 2021 with 219 respondents. Data analysis was performed using the SmartPLS 3.0 application by the PLS-SEM data analysis approach. The result was that interestingness was positively correlated with both cognitive image and affective image. In contrast, relevancy was positively correlated with the cognitive image. This study will contribute to improving the Greater Bandung destination image hence increasing tourist intents to visit Greater Bandung and thus contributing as a post-Covid-19 pandemic tourism recovery plan.Keywords: Covid-19, Destination Image, Greater Bandung, Information Quality, TikTok, Tourism